A laminar-flow based microfluidic microbial three-electrode cell for biosensing. (1st May 2016) - Li, Feifang; Zheng, Zhanwang; Yang, Bin; Zhang, Xingwang; Li, Zhongjian; Lei, Lecheng
Abstract: Microbial three-electrode cells (M3Cs) have been widely used as a promising platform for developing biosensors and studying electrochemically active bacteria (EAB). Compared to conventional microbial two-electrode cells (e.g. microbial fuel cells and microbial electrolysis cells), M3Cs can offer more stable and better defined electrochemical environments for various research purposes. This work focused on developing a microliter scale microfluidic M3C, which had unique advantages over bench scale M3Cs. In this microfluidic M3C with a built-in three electrode system, laminar flow was exploited to separate the reference electrode from the working and the counter electrodes. Using laminar flow made it possible to integrate the M3C with a microliter scale microfluidic chip and maintain a stable Ag/AgCl electrode potential. With the help of the integrated three-electrode setup, the working electrode potential of the microfluidic M3C was able to be accurately controlled and thus a well-defined electrochemical environment was provided to Geobacter sulfurreducens to respire on the electrode. During 30 days operation, the reference electrode potential was stable, which guaranteed the accurate control of the working electrode potential. By taking advantage of the microliter scale and a short hydraulic retention time (HRT), fast responses to ferric citrate and formaldehyde with good reproducibility were achieved. Furthermore, a linear relationship between the output signals (peak area) and chemicals concentrations was obtained. The microfluidic M3C developed in this work will provide researchers in related areas a versatile platform for biosensor and EAB study.